Molecular Phylogeny Restores the Supra-Generic Subdivision of Homoscleromorph Sponges (Porifera, Homoscleromorpha). - Gazave, E.; Lapébie, P.; Renard, E.; Vacelet, J.; Rocher, C.; Ereskovsky, A.V.; Lavrov, D.V.; Borchiellini, C. (PLoS ONE, 2010)
Background: Homoscleromorpha is the fourth major sponge lineage, recently recognized to be distinct from the Demospongiae. It contains ,100 described species of exclusively marine sponges that have been traditionally subdivided into 7 genera based on morphological characters. Because some of the morphological features of the homoscleromorphs are shared with eumetazoans and are absent in other sponges, the phylogenetic position of the group has been investigated in several recent studies. However, the phylogenetic relationships within the group remain unexplored by modern methods. Methodology/Principal Findings: Here we describe the first molecular phylogeny of Homoscleromorpha based on nuclear (18S and 28S rDNA) and complete mitochondrial DNA sequence data that focuses on intergeneric relationships. Our results revealed two robust clades within this group, one containing the spiculate species (genera Plakina, Plakortis, Plakinastrella and Corticium) and the other containing aspiculate species (genera Oscarella and Pseudocorticium), thus rejecting a close relationship between Pseudocorticium and Corticium. Among the spiculate species, we found affinities between the Plakortis and Plakinastrella genera, and between the Plakina and Corticium. The validity of these clades is furthermore supported by specific morphological characters, notably the type of spicules. Furthermore, the monophyly of the Corticium genus is supported while the monophyly of Plakina is not. Conclusions/Significance: As the result of our study we propose to restore the pre-1995 subdivision of Homoscleromorpha into two families: Plakinidae Schulze, 1880 for spiculate species and Oscarellidae Lendenfeld, 1887 for aspiculate species that had been rejected after the description of the genus Pseudocorticium. We also note that the two families of homoscleromorphs exhibit evolutionary stable, but have drastically distinct mitochondrial genome organizations that differ in gene content and gene order.